Experimentos de baixo custo para o ensino de eletrostática no nível fundamental - Moreira, Rodrigo Felipe Cruz [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The experimentation in the teaching of physics has been extensively studied over the years because of its potential as a tool demonstration of physics phenomena studied in classroom. In such a perspective view of the action of apprentice student involving teaching future teachers of physics, under the Program PIBID CAPES, developed since 2009, seeks ways to improve the teaching of physics experiments using the theme chosen for the electrostatic work was . In this particular work, we report the development of the project in a State School located in the city of Rio Claro, in two rooms in the 9th grade in elementary school. It is planned with the activities of teaching physics at this level of education, look at how two different ways of displaying the contents of electrostatics in a playful way for elementary students and implement a library of experiments so that students can take the experiments to their homes

A experimentação para o ensino de física tem sido muito estudada ao longo dos anos devido ao seu potencial como ferramenta demonstrativa dos fenômenos físicos estudados em sala de aula. Em vista de tal perspectiva a ação do projeto de Iniciação a Docência que envolvem futuros professores de Física, no âmbito do Programa PIBID CAPES, desenvolvido desde 2009, busca formas de aperfeiçoar o Ensino de Física utilizando experimentos, o tema escolhido para o trabalho foi eletrostática. Neste trabalho em particular relatamos o desenvolvimento do projeto em uma escola Estadual que fica na cidade de Rio Claro, em duas salas do 9º ano do Ensino Fundamental. Pretende-se com as atividades de docência de Física neste nível de ensino, analisar duas maneiras distintas de apresentar o conteúdo de eletrostática de forma lúdica para os alunos do ensino fundamental e implementar uma biblioteca de experimentos de forma que os alunos possam levar os experimentos para suas casas
Keywords: Física - Estudo e ensino; Eletrostatica; Ensino fundamental; Fisica experimental